Revitalisation issues of settlements built in 1946-1974 in terms of social and demographic changes = Problemy rewitalizacji osiedli mieszkaniowych z lat 1946-1974 w aspekcie zmian społecznych i demograficznych - Czarnecki, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper refers to the issues of forming the revitalisation programs of settlements in particular houses built in 1946-1974 in terms of the understanding of social ? demographic changes which have been taking place in a modern society. Paragraphs 3 and 4 contain the description of general social and legal factors which influenced the shape of a family and the residential structure built in 1946-1974.
Keywords: architektura; rewitalizacja; demograficzne zmiany; osiedla mieszkaniowe; nowoczesny model rodziny; architecture; revitalisation; demography; modern family